2007
DOI: 10.1021/pr070015x
|View full text |Cite
|
Sign up to set email alerts
|

Recoverin as a Redox-Sensitive Protein

Abstract: Recoverin is a member of the neuronal calcium sensor (NCS) family of EF-hand calcium binding proteins. In a visual cycle of photoreceptor cells, recoverin regulates activity of rhodopsin kinase in a Ca2+-dependent manner. Like all members of the NSC family, recoverin contains a conserved cysteine (Cys38) in nonfunctional EF-hand 1. This residue was shown to be critical for activation of target proteins in some members of the NCS family but not for interaction of recoverin with rhodopsin kinase. Spectrophotomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 66 publications
2
32
0
Order By: Relevance
“…These data are of interest because Cys-39 is the only cysteine residue in recoverin and is strictly conserved among all members of the NCS family. Permyakov et al showed that recoverin lost the ability to react with the thiol-specific Ellman's reagent (5,5Ј-dithiobis-(2-nitrobenzoic acid)) upon incubation under non-reducing conditions, suggesting that the sulfur of Cys-39 underwent oxidation (17). For this reason, noting also that the retina is one of the most vascularized tissues in the body, they further proposed that Cys-39 may function as a redox sensor in rod photoreceptor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are of interest because Cys-39 is the only cysteine residue in recoverin and is strictly conserved among all members of the NCS family. Permyakov et al showed that recoverin lost the ability to react with the thiol-specific Ellman's reagent (5,5Ј-dithiobis-(2-nitrobenzoic acid)) upon incubation under non-reducing conditions, suggesting that the sulfur of Cys-39 underwent oxidation (17). For this reason, noting also that the retina is one of the most vascularized tissues in the body, they further proposed that Cys-39 may function as a redox sensor in rod photoreceptor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Those fractions containing recoverin were combined and concentrated with a YM-10 Centricon to 1-2 ml and then dialyzed against Buffer C at 4°C to remove EGTA. Purified protein was quantified spectrally by ⑀ 280 (WT, 24,075 M Ϫ1 cm Ϫ1 ; C39A, 24,000 M Ϫ1 cm Ϫ1 ) (17,21) and frozen at Ϫ80°C until use. Preparation of mRv-mRv was prepared from T7 Express E. coli cells coexpressing yeast N-myristoyltransferase1 in pBB131 (20) with recoverin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild oxidative environments regulate the activity of recoverin by acting on a conserved Cys residue (Cys39 in the human homolog) [195197]. Experiments using site-directed mutagenesis of Cys39 to Asp (-SO 2 H mimetic) showed that hyperoxidation of myristoylated protein did not change the affinity for Ca 2+ but drastically decreased the binding of recoverin to photoreceptor cell membranes [196].…”
Section: Redox Regulation Of Metabolismmentioning
confidence: 99%
“…Importantly, the free cysteine in position 39 (Cys39) is critically important for recoverin’s function and contributes to its ability to bind Ca 2+ . In fact, Cys39 is one of the most highly conserved residues and part of the CPXG motif in the Neuronal Calcium Sensor (NCS) family proteins10 and plays functional roles in redox sensing, dimerization, and ligand interactions1112. For example, mutation of Cys39 to aspartic acid results in a significant reduction of photoreceptor membrane affinity13.…”
mentioning
confidence: 99%